Cross-border commuting and migration intentions: the roles of risk aversion and time preference - Klaus Nowotny (Contemporary Economics, 2014)
This article analyses the effects of individual risk aversion and time preference on cross-border mobility intentions using a theoretical and empirical model. The paper extends the previous literature by considering both cross-border commuting and migration as modes of mobility. The theoretical model shows that risk aversion has a negative effect on the willingness to migrate and to commute while the effect of time preference depends on expectations about the development of future wages in the home country and abroad. The empirical model, which is based on a multinomial probit regression, confirms the hypotheses regarding risk aversion and shows that the rate of time preference has a nonlinear effect on migration and commuting intentions consistent with expectations of higher real wage growth in the home country than abroad. The analysis sheds light on how time preference and risk aversion influence mobility decisions. This is especially important for integrating border regions in the European Union, in which both migration and commuting are possible.
Keywords: F22; R23; D80; D91; J61; 330; willingness to migrate; willingness to commute; risk aversion; time preference; discount rate; migration and commuting intentions